Strategies of Care Changing Elderly Care in Italy and the Netherlands - Roit, Barbara Da (Care and Welfare Series, 2010)
This analytic study surveys the transformations of elderly care policies and practices since the early 1990s, by comparing the trajectories of two extremely different care systems: Italy, a familialistic model with no relevant changes in social policies; and the Netherlands, a formal care model under restructuring. The author demonstrates that, in spite of strong policy pressures, the Dutch system remains a formal care model and represents a case of institutional and social resistance to welfare restructuring By contrast, the Italian system has shifted from family-based to a mix of family- and market-based model, despite the absence of substantial policy intervention. She argues that the ongoing changes need to be seen from a micro-to-macro perspective, considering the choices and strategies of the actors that are limited and conditioned by the institutional framework, but also represent possible forces of social change. This title is available in the OAPEN Library - http://www.oapen.org.